A systematic review of the efficacy of ergogenic aids for improving running performance - Schubert, M. M.; Astorino, T. A. (The Journal of Strength and Conditioning Research, 2013)
Running is a common form of activity worldwide, and participants range from "weekend warriors" to Olympians. Unfortunately, few studies have examined efficacy of various ergogenic aids in runners because the majority of the literature consists of cycling-based protocols, which do not relate to running performance. The majority of running studies conducted markedly vary in regards to specific distance completed, subject fitness level, and effectiveness of the ergogenic aid examined. The aim of this article was to systematically examine the literature concerning utility of several ergogenic aids on middle-distance running (400-5,000 m) and long-distance running (10,000 meters marathon = 42.2 km) performance. In addition, this article highlights the dearth of running-specific studies in the literature and addresses recommendations for future research to optimize running performance through nutritional intervention. Results revealed 23 studies examining effects of various ergogenic aids on running performance, with a mean Physiotherapy Evidence Database score equal to 7.85 ± 0.70. Of these studies, 71% (n = 15) demonstrated improved running performance with ergogenic aid ingestion when compared with a placebo trial. The most effective ergogenic aids for distances from 400 m to 40 km included sodium bicarbonate (4 studies; 1.5 ± 1.1% improvement), sodium citrate (6 studies; 0.3 ± 1.7% improvement), caffeine (CAFF) (7 studies; 1.1 ± 0.4% improvement), and carbohydrate (CHO) (6 studies; 4.1 ± 4.4% improvement). Therefore, runners may benefit from ingestion of sodium bicarbonate to enhance middle distance performance and caffeine and carbohydrate to enhance performance at multiple distances.